Modeling Anaerobic Co-Digestion of Water Hyacinth with Ruminal Slaughterhouse Waste for First Order, modiﬁed Gompertz and Logistic Kinetic Models - Erick Omondi Auma; Peter Kuria Ndiba; Gloria Chepkoech Koech; Arnold Aluda Kegode (International Journal of Renewable Energy Development, 2023)
The co-digestion of water hyacinth (WH) with ruminal slaughterhouse waste (RSW) has the potential to improve biogas production from WH and reduce its environmental challenges. However, efficient operation of the process requires an understanding of the relationship between the biogas production and the process parameters. Kinetic models can be useful tools for describing the biogas production process in batch reactors. While the first order kinetics models assume that the rate of biogas production is proportional to the concentration of the remaining substrates, other models such as the modiﬁed Gompertz and the Logistic models incorporate the lag phase, which is a key feature of the anaerobic digestion process. This study conducted batch co-digestion of WH with 0, 10, 20 and 30% RSW proportions at mesophilic temperature of 32ºC. Co-digestion of WH with 30% RSW proportion exhibited the most stable daily biogas production and the largest biogas yield in 50 days. The biomethanation data were fitted with the first order kinetics, modiﬁed Gompertz and the Logistic models. The biogas production for co-digestion of WH with 30% RSW was best described by the modified Gompertz model with a biogas yield potential, Mo, of 43.2 ml (gVS)-1d-1; maximum biogas production rate, Rm, of 1.50 ml (gVS)-1d-1; and duration of lag, λ, of 3.89 d.